The Zap-X Radiosurgical System in the Treatment of Intracranial Tumors: A Technical Case Report. Issue 4 (13th January 2021) - Pan, Longsheng; Qu, Baolin; Bai, Jingmin; Huang, Lichao; Wang, Jinyuan; Wang, Chengcheng; Dai, Xiangkun; Weidlich, Georg; Adler, John R
Abstract: BACKGROUND AND IMPORTANCE: The Zap-X system (Zap Surgical Systems Inc, San Carlos, California) is a radically new surgical robot designed for brain and head and neck radiosurgery. It represents the first new dedicated brain stereotactic radiosurgery platform in almost half a century optimizing the goals of safety, speed, and accuracy. The Zap-X system was used in a required Chinese National Medical Products Administration clinical study. In early January 2020, 2 patients were treated with the Zap-X robot prior to a national COVID-19 lockdown. Both were closely followed via clinical exam and magnetic resonance imaging (MRI) imaging. Prospectively collected data were used to generate this report. CLINICAL PRESENTATION: Two female patients, each harboring either a trigeminal schwannoma or petroclival meningioma, were treated with the Zap-X robot. Respective tumor volumes were 2.60 and 4.02 cm 3 . A radiation dose of 13 Gy was prescribed to the 50% isodose line. At 8 mo of follow-up, preoperative symptoms were either resolved or stable and MRI imaging demonstrated a 31% and 56% reduction in lesion volume, respectively. In both patients, symptoms improved, and tumor volumes decreased, whereas no major complication was observed. CONCLUSION: Given only 2 patients and short-term follow-up, any conclusions about the safety and efficacy of the Zap-X radiosurgery robot are preliminary. However, in the absence of any other published outcomes to date, this small case series may be of interest to many radiosurgical specialists.